Synthesis and antibacterial activity of new 9-O-arylpropenyloxime ketolides - Nam, Ghilsoo; Kim, Yang Soo; Choi, Kyung Il (Pergamon Press Ltd., 2010)
A novel series of 9-O-arylpropenyloxime ketolide was synthesized and evaluated for their antibacterial activity. This series of ketolide exhibited potent activity against clinically isolated gram-positive strains including Staphylococcus pneumoniae and Straptococcus Pyogenes. (C) 2010 Published by Elsevier Ltd.
Keywords: STREPTOCOCCUS-PNEUMONIAE; TELITHROMYCIN; SUSCEPTIBILITY; DERIVATIVES; RESISTANT